Knowledge, attitudes and practices of healthcare professionals in the management of patients with hypertension and concurrent bronchial asthma: a cross-sectional study in the Yellow River Delta region of China - Yang Yang; Wenwen Xu; Fei Yu; Xiaohong Yan; Xingbin Ma; Jinxiang Gao (BMJ Open)
Objective To assess the Knowledge, Attitudes and Practices (KAP) among healthcare professionals in managing patients with coexisting hypertension and bronchial asthma.Design A cross-sectional survey. The reporting of this study followed the Strengthening the Reporting of Observational Studies in Epidemiology checklist.Setting From 30 March to 15 April 2024 at 66 various level hospitals and community health service centres.Participants Physicians and nurses specialising in clinical internal medicine, each with over 2 years of practice and who provided informed consent.Primary and secondary outcome measures The demographic characteristics of the healthcare professionals and their KAP towards the Management of Patients with Hypertension and Concurrent Bronchial Asthma were collected using a self-administered questionnaire. The primary outcome was the KAP scores. The secondary outcomes were the factors associated with the KAP scores and how the KAP dimensions interacted among them.Results The study involved 586 valid questionnaires collected from participants. Participants’ median KAP scores were as follows: knowledge – 8 (IQR: 6–9), attitude – 31 (29-34) and practice – 41 (36-46) on scales ranging from 0 to 12, 7 to 35 and 12 to 60, respectively. Multivariate logistic regression analysis showed having a Bachelor’s degree or higher education (OR=0.614; 95% CI (0.421, 0.896); p=0.011), and a knowledge score ≥8 (OR=2.130; 95% CI (1.527, 2.973); p<0.001) significantly predicted adherence to recommended practices. Structural equation modelling revealed significant direct effects between knowledge and attitude (β=0.578, p=0.010) and between knowledge and practice (β=0.221, p=0.010). However, the direct link between attitude and practice (β=0.162, p=0.052) and indirect effect of knowledge on practice via attitude (β=0.094, p=0.052) were not statistically significant.Conclusions Healthcare professionals exhibited limited knowledge, positive attitudes but suboptimal practices when managing patients with comorbid hypertension and bronchial asthma. It is crucial to develop targeted educational interventions and continuous professional development programmes to improve clinical outcomes in this patient population.